ANALISIS PENGENDALIAN DEBIT BANJIR SUNGAI JINGAH KECAMATAN LAMPIHONG KABUPATEN BALANGAN - Gusti Surya Rifani (Jurnal Teknologi Berkelanjutan, 2014)
The flood in Jingah River is one of the natural phenomena. The flood in Jingah River is caused by the high rate rain and it causes the changing of the land use and many other problems. The special target of this research is to formulate the effective ways to control the flood in Jingah River. In order to do research on the flood and to achieve the target of this research, the primary data are the data from the field measurement and the secondary data are the topography map and geometric data of Jingah River, and any other supporting data. The stages of the flood research are devided into 2 parts: hydrology analysis and hydraulic analysis. The counting result of the peak volume of the flood will use synthesis unit hydrograph with Nakayasu method, model HEC –RAS 4.1.0 will be used for hydraulic analysis. The result of the flood research is the overflow flooded area. Next, there will be done the flood control as civil works efforts which has simulated into HER-RAS 4.1.0 model with the flood volume that can be reduced on the flooded area as its result. Based on simulation result, the flood happen and re-happen within 2 years. The flood controlling efforts is done by normalizing within 50 years and the simulation result shows that there is some significant changes in form of flood reduction up to 80%.